KEANEKARAGAMAN JENIS IKAN AIR TAWAR KAWASAN BENDUNGAN MEROWI DAN SEKITARNYA DI DESA SEMAYANG KECAMATAN KEMBAYAN KABUPATEN SANGGAU - Sri, Muliana; Prayogo, Hari; Widiastuti, Tri (Universitas Tanjungpura, 2024)
Merowi dam is the only dam (reservoir) located in Semayang Village, Kembayan District, Sanggau Regency, West Kalimantan Province. The merowi dam was built using Sanggau APBD funds. This study aimed to obtain data on the diversity of freshwater fish species upstream, downstream and around the Merowi Dam, Semayang Village, Kembayan District, Sanggau Regency. This research used survey method. Determination of stations was purposive sampling, where fish sampling was carried out using the catch per unit effort method (Saputra, 2018). Based on the data and research results, six stations obtained 19 types of freshwater fish belonging to 8 families. The dominance index value of the six stations ranged from (C) = 0.21- 0.33, which means that no fish dominates the other species fish. The value of species diversity from the six stations ranged from (H') = 1.28